Genetic Association Between Androgen Receptor Gene CAG Repeat Length Polymorphism and Male Infertility: A Meta-Analysis. Issue 10 (March 2016) - Pan, Bihui; Li, Rui; Chen, Yao; Tang, Qiuqin; Wu, Wei; Chen, Liping; Lu, Chuncheng; Pan, Feng; Ding, Hongjuan; Xia, Yankai; Hu, Lingqing; Chen, Daozhen; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The association between polymorphism of androgen receptor gene CAG (AR-CAG) and male infertility in several studies was controversial. Based on studies on association between AR-CAG repeat length and male infertility in recent years, an updated meta-analysis is needed. We aimed to evaluate the association between AR-CAG repeat length and male infertility in advantage of the data in all published reports. We searched for reports published before August 2015 using PubMed, CNKI, VIP, and WanFang. Data on sample size, mean, and standard deviation (SD) of AR-CAG repeat length were extracted independently by 3 investigators. Forty-four reports were selected based on criteria. The overall infertile patients and azoospermic patients were found to have longer AR-CAG repeat length (standard mean difference (SMD) = 0.19, 95% confidence interval (CI): 0.10–0.28, P < 0.01; SMD = 0.36, 95% CI: 0.10–0.61, P < 0.01). AR-CAG repeat length was longer in infertile men in Asian, Caucasian, and mixed races (SMD = 0.25, 95% CI: 0.08–0.43, P < 0.01; SMD = 0.13, 95% CI: 0.02–0.25, P < 0.05; SMD = 0.39, 95% CI: 0.15–0.63, P < 0.01). The overall study shows that increased AR-CAG repeat length was associated with male infertility. The subgroup study on races shows that increased AR-CAG repeat length was associated with male infertility in Asian, Caucasian, and mixed races. Increased AR-CAG repeat length was also associated with azoospermia. This meta-analysis supports that increased androgen receptor CAG length is capable of causing male infertility susceptibility.